The interplay between the suprafacial and intrafacial mechanisms for complete methane oxidation on substituted LaCoO3 perovskite oxides - Wang, Ting (2021)
The rational design of efficient catalysts can be guided by identifying proper descriptors that can rationalize and predict the catalytic behaviors. This study presents the feasibility of using the relative position between O p-band center and B-site metal cation d-band center as an activity descriptor for methane oxidation over LaCoO3 perovskite oxides. Experiments on B-site substituted LaFexCo1-xO3 perovskite oxides revealed that the relative positions between the two band centers governed the catalytic comportment. The suprafacial model-driven catalysts with negative relative position values exhibited exceeding activity at low temperatures; Inversely, the intrafacial model-driven catalysts with positive relative position values, showed superior activity at high temperatures. These findings were found to be effective on the A-site substituted La1-xSrxCoO3 perovskite oxides for catalytic performance prediction. This work hence showcases a promising principle to design highly active perovskite catalysts suitable for oxidation reactions.